Utilización del factoring y su influencia en la gestión financiera de las micro y pequeñas empresas del distrito de Chocope de la provincia de Ascope año 2016 - Cieza Calderón, Ivonne (2017)
This research seeks to answer the question of whether factoring should be used in the financial management of Micro and Small Enterprises (MYPES) in the Chocope district of the province of Ascope, as entrepreneurs of these companies undertake large Financing that allows them to obtain the immediate cash in the short term and meet their obligations and at the same time improve the performance of their financial management and therefore continue with the business in progress, so the objective of this study is to demonstrate the influence that would have The correct application of factoring for the financial management of the above-mentioned MYPES, taking into account whether they actually use factoring through a survey carried out on the sample under study, also considering the conditions, requirements, rates, etc. With a view to highlighting the importance of this factoring especially to the financial management of these MYPES in the Chocope district of the country. Province of Ascope. In addition, in order to elaborate the present research study, the Descriptive and Synthetic methods have been used. Data collection techniques such as survey and bibliographic research, treatment techniques and analysis of information such as document analysis, Tabulation of tables, formulation of graphs, extraction of abstracts and bibliographic review and data processing techniques such as sorting and classification and computerized process, and even non-experimental and cross-sectional research design was used, since the variables Were not manipulated and the data were obtained in a single moment. Finally, it was concluded that the use of factoring does influence the financial management of the MYPES of the Chocope district of the province of Ascope in 2016.